2019
DOI: 10.1080/16184742.2019.1620304
|View full text |Cite
|
Sign up to set email alerts
|

The perceived influence of sports betting marketing techniques on disordered gamblers in treatment

Abstract: Research question: The proliferation of marketing stimuli to gamble on sports is a growing concern in many jurisdictions. However, little is known about the perceived influence of marketing among the most severe group of problem gamblers (i.e., those receiving treatment). This study aims to explore how problem sports bettors perceive gambling marketing is affecting them. Research methods: It examines the opinions of 43 sports bettors undergoing treatment for gambling disorder. Seven qualitative focus groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Advertisers generate audience engagement by using technologies to reach customers with highly relevant advertisements based on what they do, while placing advertisements adjacent to contents expected to be visited by target consumers (Wang 2006). These findings also support the recent evidence that has reported that bonuses, including price-related gambling promotions, have been found to be particularly persuasive for encouraging gambling behavior for those experiencing gambling-related problems (Lopez-Gonzalez et al 2020).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Advertisers generate audience engagement by using technologies to reach customers with highly relevant advertisements based on what they do, while placing advertisements adjacent to contents expected to be visited by target consumers (Wang 2006). These findings also support the recent evidence that has reported that bonuses, including price-related gambling promotions, have been found to be particularly persuasive for encouraging gambling behavior for those experiencing gambling-related problems (Lopez-Gonzalez et al 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Other research has reported that both treatment-seeking sports bettors and general population sports bettors were encouraged to spend more due to advertising, particularly in response to free bet and deposit offers (Hing et al 2015). In a sample of Spanish sports bettors undergoing treatment for gambling disorder (n = 43), several promotions including bonuses, enhanced odds, and money back promotions were found to be particularly persuasive forms of marketing techniques used by gambling operators (Lopez-Gonzalez et al 2020).…”
mentioning
confidence: 94%
“…Furthermore, next to personal and socio-cultural influences, we advocate forthcoming studies to examine equally important political, legal, and commercial normalization mechanisms [ 19 ]. For example, different sources encourage scholars to engage in research on the impact of gambling sponsorships and advertisement in professional sports clubs on the normalization of gambling [ 6 , 18 , 20 ]. Building on—and integrating–normalization and institutional theory could provide a richer understanding of the dominant norms and logics underpinning gambling’s firm place in sports and society [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above, much scholarship has already emphasized the close relationship between sports on the one hand and gambling (in general) and sports betting (in particular) on the other hand. Sports as an institution has thereby been shown to be an ideal vehicle to promote sports betting products, for instance through advertising and marketing during sports events, and (shirt) sponsorship in sports organizations [ 5 , 6 , 9 , 13 , 16 , 20 ]. Some academics point to potential positive outcomes of recreational gambling on stress levels and life satisfaction [ 21 , 22 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, connatural features of personalization in gambling such as geolocation have also been examined in terms of player data protection and privacy [17] . Personalized marketing can be damaging for those who are experiencing gambling problems, especially in those instances in which problem gamblers who are trying to cut down or discontinue gambling continue to receive commercial marketing enticements [18] . Nevertheless, here, the focus is specifically on customization-related implications.…”
Section: A Closer Look At Responsible Gambling Implications Of Custommentioning
confidence: 99%